Assessing the Effect of Pretreatments on the Structure and Functionality of Microbial Communities for the Bioconversion of Microalgae to Biogas - Córdova, Olivia; Chamy, Rolando; Guerrero, Lorna; Sánchez-Rodríguez, Aminael (Frontiers in Microbiology, 2018)
Microalgae biomethanization is driven by anaerobic sludges and generally limited by the incomplete hydrolysis of the wall of these organisms and therefore, by the low availability of microalgal biomass for the methanogenic community. The application of enzymatic pretreatments, e.g. hidrolytic enzymes, is among the strategies used to work around this limitation. Despite these pretreatments proven efficiency in increasing biomethanization, the changes that a given pretreatment may cause to the structures of microbial communities, i.e. functionally active species, of anaerobic sludge during biomethanization are still unknown. This study evaluated the changes in the expression of the metatranscriptome of microalgae communities of anaerobic sludge during the biomethanization of Chlorella sorokiniana without pretreatment (control) and pretreated with cellulase in order to increase the solubilization of organic matter. Pretreated microalgal biomasses experienced significant increases in the production of biogas. At the level of the metatranscriptome, the control samples showed that the microalgae cells are functionally active and that the methanogenic community is dominated by γ- and δ- proteobacteria, such as Methanospirillum hungatei. In contrast, the pretreated samples were characterized by the absence of active microalgae cells and a bacteria population dominated by species of the Clostridia class. These differences are also related to the differential activation of metabolic pathways/routes associated with the degradation of organic matter to its biomethanization.